From Pathophysiology to Treatment of Huntington's Disease - Szejko, Natalia (IntechOpen, 2022)
Huntington's Disease (HD) is a progressive neurodegenerative disease leading to a variety of neurological and psychiatric symptoms such as chorea, parkinsonism, oculomotor symptoms, cognitive decline, depression, suicidal ideation, and psychosis. Currently, only symptomatic treatment is available. In recent years, there has been a growing number of publications regarding pathophysiology, disease biomarkers, and possible avenues for causal therapy of HD. This book presents an overview of the most important research updates in the pathophysiology and treatment of HD, with particular reference to advances in HD neuropathology, neuroimaging, and biomarkers of HD. We also summarize possible new therapeutic targets, including cannabis-based medicine, cellular, and cell-free therapeutics. Importantly, researchers from different regions of the world have contributed to this volume as we wanted to create a balanced, inclusive, and interdisciplinary review of the topics. We hope that with this book readers will be offered a compact summary of up-to-date trends in HD research which, ultimately, will enable better diagnosis and treatment for HD patients.